Macroalgae and Microalgae Biomass as Feedstock for Products Applied to Bioenergy and Food Industry: A Brief Review - Michelle Dias Hornes da Rosa; Cristina Jansen Alves; Felipe Nardo dos Santos; Alexander Ossanes de Souza; Elessandra da Rosa Zavareze; Ernani Pinto; Miguel Daniel Noseda; Daniela Ramos; Cláudio Martin Pereira de Pereira (Energies, 2023)
This article is a brief and critical review of the state of the art in algae production in the food and energy industries. Review and experimental articles from the last five years were selected to recapitulate the reasons for interest in algae cultivation, for which we highlight the most valuable phytochemicals passing through their niches in the food market, their bioenergetic potential and the possible uses of algal waste biomass. In addition, we punctuate the advent of algae biorefineries. The objectives of this study were to list the main points related to interest in cultivation, drawing a parallel between the establishment of algae in the food market and its potential to establish itself in the energy market. It was concluded that the use of algae biorefineries has been used as a solution for the food, chemical and energy markets, despite the need for the development of broader research on industrial scale.